Executive Succession: Past, Present & Future - Kesner, Idalene F.; Sebora, Terrence C. (Journal of Management, 1994)
In this study we review over thirty years of succession research in an effort to discern what we know conclusively about the subject, what we do not know because of mixed results, and what has not yet been studied. We begin by answering two key questions: (1) Why is succession such an important topic? and (2) What makes CEO succession different from other types of turnover? Next, we explore the three key stages of succession research. The first phase covers the period from the 1950s to the 1960s. This period is best described as the emergence of the field. The second phase, covering the 1970s reflects a period of theory building and empirical investigation. The final phase from the 1980s to the present is characterized by review and explosive growth. Following our review, we use these combined studies to create an overall model of succession-a model designed to offer prescriptions as to where researchers have been and where they should be going in the future.